The ethical issues regarding consent to clinical trials with pre-term or sick neonates: a systematic review (framework synthesis) of the empirical research. Issue 1 (December 2015) - Wilman, E.; Megone, C.; Oliver, S.; Duley, L.; Gyte, G.; Wright, J. M.
Abstract Background Conducting clinical trials with pre-term or sick infants is important if care for this population is to be underpinned by sound evidence. Yet approaching parents at this difficult time raises challenges for the obtaining of valid informed consent to such research. This study asked: what light does the empirical literature cast on an ethically defensible approach to the obtaining of informed consent in perinatal clinical trials? Methods A systematic search identified 49 studies. Analysis began by applying philosophical frameworks which were then refined in light of the concepts emerging from empirical studies to present a coherent picture of a broad literature. Results Between them, studies addressed the attitudes of both parents and clinicians concerning consent in neonatal trials; the validity of the consent process in the neonatal research context; and different possible methods of obtaining consent. Conclusions Despite a variety of opinions among parents and clinicians there is a strongly and widely held view that it is important that parents do give or decline consent for neonatal participation in trials. However, none of the range of existing consent processes reviewed by the research is satisfactory. A significant gap is evaluation of the widespread practice of emergency 'assent', in which parents assent or refuse their baby's participation as best they can during the emergency and later give full consent to ongoing participation and follow-up. Emergency assent has not been evaluated for its acceptability, how such a process would deal with bad outcomes such as neonatal death between assent and consent, or the extent to which late parental refusal might bias results. This review of a large number of empirical papers, while not making fundamental changes, has refined and developed the conceptual framework from philosophy for examining informed consent in this context.